Airborne particle number profiles, particle mass distributions and particle-bound PAH concentrations within the city environment of Basel: an assessment as part of the BRISKA Project - Junker, M.; Kasper, M.; Röösli, M.; Camenzind, M.; Künzli, N.; Monn, Ch; Theis, G.; Braun-Fahrländer, Ch (Atmospheric environment (1994), 2000)
A project aimed at assessing a variety of particulate indicators was carried out at three locations in the city of Basel within the scope of the Basel Air Quality Risk Assessment Project (BRISKA). Size specific particle number concentrations (0.018–0.421 μm), particle mass distributions (0.04–49 μm), and particle-bound polycyclic aromatic hydrocarbon (pPAH) concentrations were measured. Locations differed in housing and traffic characteristics. For particle number and pPAH concentrations, one separate continuous 27–28-h measurement was performed at each location. Simultaneously, non continuous measurements assessing the particle mass distribution were performed. Distinct day profiles corresponding to the diurnal traffic profile were observed for absolute particle numbers and pPAH concentrations. The number of ultrafine particles as well as pPAH concentrations were more closely correlated to the number of heavy duty vehicles ( r=0.67–0.86 and 0.85–0.90), respectively, than to the number of light duty vehicles ( r=0.43–0.59 and 0.64), respectively. The highest particle number concentrations were found in the ultrafine particle mode (<0.1 μm) averaging between 82–87% of the total particle numbers <0.421 μm while the accumulation mode (0.1–2.8 μm) made up for most of the particle mass (mean >82%). For size specific absolute mass concentrations, the highest concentrations were generally found in the early morning and evening hours. The mass distribution within the accumulation mode differed from rush hour episodes, in between rush hour episodes and a lawn mowing episode.